A new technique for stain-marking of seeds with safranine to track seed dispersal and seed bank dynamics - Zhang, Zheng; Shi, Xinglei; Li, Ruhai; Qiang, Sheng (Frontiers in Plant Science, 2022)
Accurate tracking of seed dispersal is critical for understanding gene flow and seed bank dynamics, and for predicting population distributions and spread. Available seed-tracking techniques are limited due to environmental and safety issues or requirements for expensive and specialized equipment. Furthermore, few techniques can be applied to studies of water-dispersed seeds. Here we introduce a new seed-tracking method using safranine to stain seeds/fruits by immersing in (ex situ) or spraying with (in situ) staining solution. The hue difference value between pre- and post-stained seeds/fruits was compared using the HSV color model to assess the effect of staining. A total of 181 kinds of seeds/fruits out of 233 tested species of farmland weeds, invasive alien herbaceous plants and trees could be effectively stained magenta to red in hue (320°–360°) from generally yellowish appearance (30°–70°), in which the other 39 ineffectively-stained species were distinguishable by naked eye from pre-stained seeds. The most effectively stained seeds/fruits were those with fluffy pericarps, episperm or appendages. Safranine staining was not found to affect seed weight or germination ability regardless of whether seeds were stained ex situ or in situ. For 44 of 48 buried species, the magenta color of stained seeds clearly remained recognizable for more than 5 months after seeds were buried in soil. Tracking experiments using four species (Beckmannia syzigachne, Oryza sativa f. spontanea, Solidago canadensis and Acer buergerianum), representing two noxious agricultural weeds, an alien invasive plant, and a tree, respectively, showed that the safranine staining technique can be widely applied for studying plant seed dispersal. Identifying and counting the stained seeds/fruits can be executed by specially-complied Python-based program, basing on OpenCV library for image processing and Numpy for data handling. From above results, we conclude that staining with safranine is a cheap, reliable, easily-recognized, automatically-counted, persistent, environmentally safe and user–friendly tracking-seed method. This technique may be widely applied to staining most of the seed plant species and the study of seed dispersal in arable land, and in disturbed and natural terrestrial or hydrophytic ecological systems.